"THE EFFECT OF MONEY ETHICS, TAX MORALE, TAX FAIRNESS AND RELIGIOSITY ON TAX EVASION" - Muliani .; Luhgiatno . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
Tax evasion is a deliberate and illegal action that reports the amount of tax obligations that is incomplete and inaccurate. Tax evasion occurs when a person or organization intentionally does not comply with their responsibilities. several reasons that led to tax evasion are taxpayers' perception of high tax rates, lack of fairness in the taxation system, lack of honesty, tax revenue used for general state expenditure and others. The gap gap shows that tax evasion practices in Indonesia are increasing from year to year. Based on the Global Financial Integrity (GFI) report from 2004 - 2013, Indonesia ranks ninth as one of the countries that source illicit funds with an average of US $ 18,071 million. The research objective is to examine and analyze the effect of money ethics, tax morale, tax fairness and religiosity on tax evasion.The research method uses causality, the data used are primary data. Data collection procedures are carried out by distributing questionnaires distributed to respondents. The population used in this study were all SMEs in the city of Semarang in 2020 with a total of 1,096 UKM, the sampling technique used purposive sampling and non-probability methods using the Slovin formula to obtain 92 UKM. Data analysis techniques using descriptive statistical analysis, the validity and reliability of the data, the classic assumption test, multiple linear regression analysis and hypothesis testing with the help of SPSS 24.The results of the study include, there is a positive influence of money ethics  and tax fainess on tax evasion , there is a negative effect of tax on tax avoidance, and there is no effect of religiosity on tax evasion. The results of the determination coefficient of the research model amounted to 88.5%. The next research suggestion is to add the independent variable and possibly the intervention and moderation variables in the tax evasion research.